Improving Nutritional Outcomes (Taylor & Francis, 2025)
This book engages with the critical issue of nutrition and its relationship with the full spectrum of human development challenges in India. It examines concerns around both undernutrition and overnutrition through a range of case studies, documenting key interventions and strategies implemented by governments, NGOs, and other stakeholders. The book broadly discusses macroeconomic and social issues affecting India’s progress in addressing nutrition challenges, linking them to mesoand micro-level factors—from food and health systems to grassroots realities. It explores not only policy imperatives but, more importantly, the processes and mechanisms necessary to achieve them. Special attention is given to the role of women and women’s collectives, the importance of comprehensive, decentralized, and community-based approaches to improving nutrition among the most vulnerable, and the critical life phases that require targeted interventions. The volume also presents large-scale, state-led, and statewide models and strategies, offering valuable insights for policymakers, governments, and institutions grappling with similar issues. Part of the Innovations, Practice and the Future of Public Policy in India series, this open access volume will interest policy professionals, administrators, academics, and researchers working in public health, nutrition and dietetics, allied health, health and social care, health and development, public policy, social policy, and South Asian studies.